Electrical Resistivity Tomography and Boreholes Data to Investigate the Near-Surface Structure under the Campus Area of Çanakkale Onsekiz Mart University, Çanakkale, Turkey (Türkiye) - Co ̧skun, Nart; Çakır, Özcan; Kutlu, Yusuf Arif; Erduran, Murat (Journal of Applied Geology, 2024)
We study the soil foundation underneath the Çanakkale Onsekiz Mart University (ÇOMU) campus, Çanakkale, Türkiye by employing the electrical resistivity tomography – ERT supported by 27 boreholes data. The studied area taking place in southwest Marmara region was historically affected by large earthquakes () created by the North Anatolian Fault system. The boreholes data show that the near surface structure beneath the ÇOMU campus is made of mostly silty sands and marls. A high sensitivity resistivity instrument is used to collect the field data in which nine ERT profiles reaching lengths as long as 315 m are utilized. The current geoelectrical measurements are simulated by using two numerical models to estimate the inversion depth sensitivity from which it is found satisfactory in the depth range 0-30 m and then somewhat decreasing. The observed electrical resistivity values are in the range 2-160 W m. The geoelectrical structure corresponding to the silty sands are represented by low resistivities (<20 W m) while the high resistivity (>40 W m) depth sections are associated with the marl units. The resistivity structure beneath the ÇOMU campus is complex where both low and high resistivity depth sections reside side by side. The groundwater and clay mineralogy contribute to the broad changes in the subsurface resistivities. The groundwater flow below the steep terrain of the ÇOMU campus causes low resistivities (<10 W m) deeper than 10-m depth. The boreholes data superimposed on the two-dimensional (2-D) ERT profiles show consistency with the resistivity-depth distributions at corresponding depths.